ETHNIC CONFLICT: AN OVERVIEW OF POST-SOVIET RUSSIA - Ranjan, Sanjiv; Kant, Shashi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
After the de-centralisation and collapse of the Soviet Union, the aftermath brought chaos, and the major challenge was the manifestation of serious conflict on ethnic lines. The emergence of the Russian Federation was not peaceful, and violence remained a core character in the making of the Russian Federation in the aftermath of Post Soviet Russia. The series of issues brought major ramifications of newly formed states carved out from the large Society federation as an independent entity. The collapse of the Soviet federation created fifteen independent states amidst ethnic tension across the federation. The outcome was chaos, political disintegration and struggle for autonomy in the making of power transition.